CHARACTERISATION AND ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLES SYNTHESIZED BY ASPERGILLUS SP. - K. SUBHA RAJAM,; MARY ESTHER RANI,; R.GUNASEELI,; M.HUSSAIN MUNAVAR, (International Journal of Pharma and Bio Sciences, 2013)
The use of microorganisms in the synthesis of nanoparticles emerges as an ecofriendly approach. The microorganisms such as bacteria, fungi and actinomycetes and plant materials are used in the biosynthesis of nanoparticles. The biological synthesis of silver nanoparticles has many advantages over physical and chemical methods. In the present study, the isolated fungal strain Aspergillus sp. was used for silver nanoparticle synthesis. Cell free filtrate of isolated Aspergillus sp. was incubated with 1mM silver nitrate on a rotary orbital shaker at 120 rpm. The nanoparticles synthesis was visually observed by brown color change. The formation of silver nanoparticles was monitored by UV-Visible spectroscopy and further characterized by SEM, EDAX, Particle size and Photoluminescence analysis. The nanoparticles exhibited a maximum absorbance at 422nm in UV-Visible spectroscopy corresponding to the plasmon resonance of silver nanoparticles. SEM analysis reveals the nanoparticles with the size range of 40-70nm. The antibacterial effect of silver nanoparticles reported herein reveal its importance in advantage over conventional antibiotic against Pseudomonas aeruginosa.